2013
DOI: 10.1080/19443994.2012.700042
|View full text |Cite
|
Sign up to set email alerts
|

Microfiber filtration of lake water: impacts on TEP removal and biofouling development

Abstract: A B S T R A C TBiofouling is a major and very expensive problem for the water industry. An Amiad Automatic Microfiber Filter (AMF) was tested as a pretreatment for biofouling growth inhibition using a lake water source. The filtration efficiency of the AMF in reducing Transparent Exopolymer Particles (TEP) and chlorophyll (Chl) levels in the feedwater was measured in 24 experiments during 2010-2011. These experiments showed significant reductions in TEP (mean 47 ± 21%), Chl (mean 90 ± 6%), total suspended soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…178,179 TEP removal was moderate (47 ± 21%) while the system had a retention of 93% for Chl a. 179 EPS and cell biovolumes measured downstream on glass coupons were also reduced by 63 ± 31% and 44 ± 20%, respectively. Using an AMF system, Lakretz et al recently reported that planktonic microbial composition remains unchanged, while biofilm composition has changed significantly.…”
Section: Recent Developments For Tep Removalmentioning
confidence: 93%
See 1 more Smart Citation
“…178,179 TEP removal was moderate (47 ± 21%) while the system had a retention of 93% for Chl a. 179 EPS and cell biovolumes measured downstream on glass coupons were also reduced by 63 ± 31% and 44 ± 20%, respectively. Using an AMF system, Lakretz et al recently reported that planktonic microbial composition remains unchanged, while biofilm composition has changed significantly.…”
Section: Recent Developments For Tep Removalmentioning
confidence: 93%
“…Eshel et al described an automatic microfiber filter (AMF) design with a nominal cutoff ranging between 2 and 20 μm. , TEP removal was moderate (47 ± 21%) while the system had a retention of 93% for Chl a . EPS and cell biovolumes measured downstream on glass coupons were also reduced by 63 ± 31% and 44 ± 20%, respectively.…”
Section: Recent Developments For Tep Removalmentioning
confidence: 99%